Cover Feature: Modulation of Src Kinase Activity by Selective Substrate Recognition with Pseudopeptidic Cages (Chem. Eur. J. 37/2021). Issue 37 (9th June 2021) - Tapia, Lucía; Solozabal, Naiara; Solà, Jordi; Pérez, Yolanda; Miller, W. Todd; Alfonso, Ignacio
Abstract : The modulation of the activity of tyrosine kinases (TK) is an appealing topic of current research. This work presents new pseudopeptidic cages that protect the substrates from the action of the TK enzyme, precluding the corresponding Tyr phosphorylation, with a very good correlation between the Tyr caging and the kinase inhibition. The results illustrate how TK signaling can be efficiently and selectively modulated with supramolecular complexes. More information can be found in the Full Paper by W. T. Miller, I. Alfonso, et al. (DOI: 10.1002/chem.202100990 ).